A State of Emergency as a Protection of the Constitutional System of the State, the Security of Citizens and Public Order - Golebiowska, Anna; Bartkowski, Marcin (European research studies, 2024)
Original/Value: For the purposes of this article, a multi-aspect synthetic and critical analysis of data available in the scientific literature was conducted. The proposed solutions are to contribute to raising awareness among administrative bodies to address the subject of the state of emergency, which is the state of emergency.